Hoarding international reserves versus a Pigovian tax-cum-subsidy scheme: Reflections on the deleveraging crisis of 2008-9, and a cost benefit analysis - Joshua Aizenman (University of California, Santa Cruz Institute for International Economics (SCIIE), 2010)
In this paper we outline a Pigovian tax-cum-subsidy scheme that deals with concerns about the costs and efficacy of hoarding international reserves (IR) as a means of self-insurance against a deleveraging crisis. We overview the degree to which IR provided self-insurance to Emerging Markets (EMs) during the 2008-9 crisis, pointing out that the fear of losing IR constrained the use of a pre-crisis IR war-chest. The crisis validates the need for external debt management policy. EMs found that their initial large stocks of IR were not enough to prevent runs on their IR and large currency depreciations, runs that were abated in some countries only with the proliferation of deep swap-lines. The experience of EMs during the crisis raises concerns regarding the efficacy of hoarding IR as means of self-insurance. We outline the case for supporting self-insurance by imposing a tax on external borrowing. We focus on a model of an emerging market, where entrepreneurs finance tangible investments via bank intermediation of foreign borrowing. Bank intermediation exposes the economy to the risk of deleveraging, inducing a costly premature liquidation of tangible investments; a risk that increases with the ratio of aggregate external borrowing to IR. In these circumstances, price taking economic agents ignore their marginal impact on the expected cost of a deleveraging crisis, and external borrowing is associated with negative fire-sale congestion externalities. We show that an optimal borrowing tax reduces the distorted activity (external borrowing), and induces borrowers to finance the precautionary hoarding of international reserves.
Keywords: F15; F21; F32; F36; G15; 330; fire-sale congestion externality; deleveraging; tax-cum-subsidy; international reserves.; Finanzmarktkrise; Währungsreserven; Steuerpolitik; Subvention; Kosten-Nutzen-Analyse; Schwellenländer